Pengaruh Penggunaan Media Komik Secara Kolase Terhadap Hasil Belajar Siswa Kelas IV Madrasah Ibtidaiyah - Anugrah, Miranda Puja; Husni, Miftahul; Nurlaeli, Nurlaeli (Limas PGMI, 2023)
The purpose of carrying out this research is to 1) find out the application of comic media in collage in the learning process for class IV at MIN 1 Ogan Ilir, 2) find out the learning results of the experimental class using comic media in collage and the learning results of the control class which did not use comic media in collage, 3) knowing student learning outcomes before and after applying the use of comic media in a collage manner in class IV MIN 1 Ogan Ilir. The research method uses a quantitative approach with an experimental design, namely True Experimental Design, the type of Pretest-Posttest Control Group Design where there are two classes as samples chosen randomly. From the research results, the control class learning results were 32.05 pretest and posttest 62.30 and the experimental class learning results were 38.65 pretest and posttest 77.05. From the results of the hypothesis, a significance value of 0.002 was obtained from a significance level of 0.05. This statement illustrates that the learning outcomes of students treated using comic media in collage are higher than the learning outcomes without treatment, so it can be concluded that in the Arts, Culture and Crafts (SBdP) lesson, the subject matter of collage artwork, there was an increase in the average score of the posttest for the experimental class and the posttest for the control class.